Pengembangan Modul IPA Kelas VI dengan Model Cooperative Learning - Moh Shobirin (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2020)
This study aims to produce a Science Module with a Class VI Cooperative Learning Model that is designed to be more interesting, to train independently, creatively and innovatively, according to students 'needs and develop students' competence, character and literacy. The development model used by Dick, Carey & Carey. The selection of this model is based on the theoretical foundation of learning design. The type of data used in this study are (1) the results of the validation of the learning design expert, and the content / material expert (2) the results of the peer testing, (3) the data from the field trial results. This analysis technique is used to process data obtained through evaluation sheets in descriptive form and measure validity using predetermined formulas. The results of the validation of the material experts reached a validity score of 3.5. While the learning design expert on teaching materials developed a validity score of 3.64. Peer Test Results for the material reached a validity score of 3.6. While the results of trials on students as a whole the validity of teaching materials reached 3.55. From the data and analysis that has been done, it can be concluded that the product development of the Natural Sciences Module with the Cooperative Learning Model can be used as teaching material in Natural Science classes VI of Primary Schools that reach validity and is very valid, and is able to develop the realm of critical thinking, creative, collaboration and able to complete problem.